Pengaruh Modal Sendiri dan Volume Usaha terhadap Sisa Hasil Usaha (SHU) pada Koperasi Karyawan Siti Khadijah RS Islam Banjarmasin - Bustani Bustani; Firdaus Firdaus (Universitas Proklamasi 45 Yogyakarta, 2020)
This study aims to examine the effect of members’ equity and business volume partially and simultaneously on the net profit as the remaining business results (SHU) of the Siti Khadijah Employee Cooperative in Banjarmasin Islamic Hospital. The object of this research is the Siti Khadijah Employee Cooperative at the Banjarmasin Islamic Hospital, South Kalimantan. The data needed in this study is secondary data, namely cooperative members’ equity, business volume, and the SHU in the period of 2010-2018. This type of research is explanatory research. The secondary data was collected through research object documentation. Next, the data were analyzed using multiple linear regression, classic assumption tests, partial and simultaneous tests, and coefficient of determination. The results of this study indicate that the members’ equity and the cooperative business volume partially and simultaneously have a positive and significant effect on the SHU. This finding adds insights to academic research on the influence of the members’ equity and cooperative business volume to the SHU of the Siti Khadijah Employee Cooperative at the Banjarmasin Islamic Hospital.